(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Malaria is a protozoal disease of worldwide importance. The causative agent, Plasmodium , is transmitted from one human being to another by the bite of Anopheline mosquito. World Health Organization (WHO) has reported the occurrence of 214 million new cases during the year 2015. Malaria is commonly associated with hematological changes; anemia and thrombocytopenia being the most common. In present study the occurrence and severity of thrombocytopenia was documented in patients with malaria. 29 patients diagnosed as suffering from malaria, were registered and platelet count was determined, along with routine investigations. Out of these 29 patients, 28 (96.5 %) were suffering from P. vivaxinfection and one (3.5%) was positive for P. falciparum. No patient showed the infection with both P. vivax and falciparum. No patient was positive for Dangue antibodies. Although presence of thrombocytopenia in febrile patients also raises suspicion of Dengue fever, in our environment it is the malaria about which we should think first. Thrombocytopenia in these patients was tolerated well and only one patient needed platelet transfusion.